Platinum chromium everolimus-eluting stent versus cobalt chromium zotarolimus-eluting stent in very late stent thrombosis: a meta-analysis of randomized controlled trials. (4th February 2022) - Baterna, J J; Susanto, A; Cheng, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Very late stent thrombosis is a rare but potentially lethal outcome for drug-eluting stents used in percutaneous coronary intervention. There is limited research currently on the occurrence of very late stent thrombosis as a complication of two most used second-generation drug-eluting stents, i.e. platinum chromium everolimus-eluting stent (PtCR-EES) and cobalt chromium zotarolimus-eluting stent (CoCr-ZES). Purpose: The study provides comparative information on the formation of very late stent thrombosis as a long-term outcome of PtCr-EES and CoCr-ZES. Results of this study may guide interventional cardiologists in decision-making regarding the choice of stent. Methods: Randomized controlled trials (RCTs) which compared stent thrombosis end point of PtCr-EES and CoCr-ZES were identified through Pubmed. Results: Data from three RCTs analyzed a total of 7, 911 participants, with 4, 574 in the PtCr-EES and 3, 324 in the CoCr-ZES. Treatment with either stent showed no significant difference in the incidence of very late stent thrombosis. Conclusion: Both stents showed comparable incidence of very late stent thrombosis. Additional RCTs are recommended to further establish the results for very late stent thrombosis. Longer follow-up is also suggested to discover more long-term outcomes.